Patient perception, actual control and KAP of their diabetic management: A comparison between patients seen at Primary Care Clinic and Tertiary Hospital - Shahar, Mohammad Arif; Mohd Rafee, Adilah Rafi'ah; Mohamad Hazim, Husna; Saiful Bahri, Aina Sharleena; Mohamad, Rizman; Tuhiran, Mohamad Fadzil (Malaysian Endocrine & Metabolic Society, 2014)
Objectives: To compare patients’ perception of their diabetic control, their knowledge, attitude and practice (KAP) of their diabetic management, HbA1C and other metabolic parameters in patients seen at a primary care centre (PCC) and tertiary hospital (TH). Methods: This was a cross sectional study involving age and sex-matched 146 patients from our PCC and 145 patients from our TH. They were interviewed using a standardized KAP questionnaire and perception on their diabetic control was documented. Anthropometric measurements were made and their most recent blood investigations were recorded. Analysis was done using SPSS 19. Results: The median age of respondents from PCC and THwere57.0(51.0,64.7) and 57.0(51.0,62.0) years respectively. Patient seen at the TH had significantly longer duration of diabetes than those seen at PCC [8.0(4.0-14.0) vs. 5.0(3.0-10.0) years]. Patients from TH has significantly more complications; amputation from diabetic foot ulcers (9.7% vs. 0.7%); chronic kidney disease (11.0% vs 0.7%); stroke (9.0% vs. 4.1%); and ischaemic heart disease (17.9% vs. 8.2%).Twenty seven percent of patient in PCC and 29% of patients in TH thought that their diabetes were well controlled. However, only 19.9% of patients in PCC and 13.9% of patients in TH had HbA1c less than 6.5%. The mean HbA1C of patients seen in PCC was significantly lower than those seen at TH (8.4 ± 2.3% vs. 9.3 ± 2.6%; p = 0.001). Patients seen in TH are more hypertensive (median BP= 148/74 mmHg) than patients in PCC (median = 130/70 mmHg), but had lower LDL-cholesterol level [1.7(0.9,2.8)mmol/L vs. 2.2(1.8, 3.1) mmol/L).There was no significant difference of KAP score between patients in PCC and HT. Conclusion: Almost a third of respondents in both groups (27% and 29%) thought that their diabetes is well controlled. However, only 20% of patient in PCC and 14% of patients in TH had HbA1C of less than 6.5%. KAP score did not differ between PCC and TH group.